Analisis Rasio Keuangan Untuk Memprediksi Pertumbuhan Laba Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Sudaryanti, Enni Sri, Dra. Mabruroh, M.M (2015)
This research aims to know the influence of the ratio LDR, CAR, ROA, NPM to profit growth. The data used in this research is secondary data in the form of financial statements. The population used is a banking company listed on the Indonesia stock exchange from 2011-2013. Sample research that used as many as 30 banking company. By using purposive sampling method. Data analysis technique used is a classic Assumption Test, multiple Linear Regression, t-test, F-test and coefficient of Determination ( R^2 ). The results obtained in this study, LDR variable obtained the results t _ (count) < t _ (table) ie-0483 < 1,731, with probability greater than 0.05 i.e. 0631 > 0.05. That is, LDR influential not significantly to profit growth. CAR variable obtained the results of t _ (count) > t _ (table) i.e. 3996 > 1,731, with smaller probabilities of 0.05 i.e. 0000 < 0.05. That is, ROA influential significantly to profit growth. ROA variable obtained the results t _ (count) < t _ (table) ie-1.975 < 1,731, with probability greater than 0.05 i.e. 0052 > 0.05. That is, ROA influential not significantly to profit growth. NPM variable obtained the results t _ (count) > t _ (table) i.e. 3973 > 1,731, with smaller probabilities of 0.05 i.e. 0000 < 0.05. That is, NPM influential significantly to profit growth. From the test results obtained simultaneously, F _ (count) > F _ (table) i.e. 20500 > 2.43, with significant value is 0.000 < 0.05. Then the equation of all free variables (LDR, CAR, ROA, NPM) together influential variables significantly to profit growth.